Tumor Necrosis Factor Induces Hyperphosphorylation of Kinesin Light Chain and Inhibits Kinesin-Mediated Transport of Mitochondria - De Vos, Kurt (The Rockefeller University Press, 2000)
The molecular motor kinesin is an ATPase that mediates plus end-directed transport of organelles along microtubules. Although the biochemical properties of kinesin are extensively studied, conclusive data on regulation of kinesin-mediated transport are largely lacking. Previously, we showed that the proinflammatory cytokine tumor necrosis factor induces perinuclear clustering of mitochondria. Here, we show that tumor necrosis factor impairs kinesin motor activity and hyperphosphorylates kinesin light chain through activation of two putative kinesin light chain kinases. Inactivation of kinesin, hyperphosphorylation of kinesin light chain, and perinuclear clustering of mitochondria exhibit the same p38 mitogen-activated kinase dependence, indicating their functional relationship. These data provide evidence for direct regulation of kinesin-mediated organelle transport by extracellular stimuli via cytokine receptor signaling pathways.